2015
DOI: 10.4236/psych.2015.65059
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Role of Decentering in the Associations between Self-Reflection, Self-Rumination, and Depressive Symptoms

Abstract: Theorists have suggested that self-focused attention has adaptive and maladaptive aspects and have proposed self-rumination and self-reflection. Previous research on self-focus and mindfulness have shown that self-rumination increases depression and counteracts decentering which is the capacity to take a detached view of one's thoughts and emotions. On the contrary, although self-reflection was defined as an adaptive type of self-focus, its contents or mode have not been examined, and the mechanism of its cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 44 publications
1
21
0
1
Order By: Relevance
“…Studies show a strong association between depressive symptoms and cognitive fusion (e.g., Cvetanovski 2014; Dinis et al 2015;Gillanders et al 2014), decentering (e.g., Bieling et al 2012; COGNITIVE FUSION'S PREDICTIVE POWER OF DEPRESSIVE SYMPTOMS 4 2007a; Fresco et al 2007b;Linares et al 2016;Mori and Tanno 2015), mindfulness (e.g., Baer et al 2008;Brown and Ryan 2003;Carmody and Baer 2008), and metacognitive dimensions (e.g., Huntley and Fisher 2016;Lashkary et al 2016;Sarisoy et al 2014). …”
Section: Concurrent Effects Of Different Psychological Processes In Tmentioning
confidence: 99%
“…Studies show a strong association between depressive symptoms and cognitive fusion (e.g., Cvetanovski 2014; Dinis et al 2015;Gillanders et al 2014), decentering (e.g., Bieling et al 2012; COGNITIVE FUSION'S PREDICTIVE POWER OF DEPRESSIVE SYMPTOMS 4 2007a; Fresco et al 2007b;Linares et al 2016;Mori and Tanno 2015), mindfulness (e.g., Baer et al 2008;Brown and Ryan 2003;Carmody and Baer 2008), and metacognitive dimensions (e.g., Huntley and Fisher 2016;Lashkary et al 2016;Sarisoy et al 2014). …”
Section: Concurrent Effects Of Different Psychological Processes In Tmentioning
confidence: 99%
“…Since the key idea of decentering is the changing of one's relationship with the contents of their thoughts and emotions, researchers have suggested that decentering mitigates rumination because decentered individuals can disengage once becoming aware of their ruminative thoughts (Teasdale et al, 2002). Consistent with this theory, past findings have shown a negative association between decentering and rumination, and decentering has been found to be negatively associated with depression (Fresco et al, 2007;McCracken, Barker & Chilcot, 2014;Mori & Tanno, 2015).…”
Section: Self-rumination and Self-reflectionmentioning
confidence: 97%
“…In contrast to self-rumination, self-reflection is considered to be positively associated with decentering (Lau et al, 2006). In a study by Mori and Tanno (2015), individuals with a higher degree of reported self-reflection revealed more decentering and less depressive symptoms. These findings lend support to the proposed hypothesis that through self-reflection, individuals can attend objectively to their inner experiences-both adaptive and maladaptive-which may allow them to more effectively regulate their thoughts and feelings.…”
Section: Self-rumination and Self-reflectionmentioning
confidence: 97%
“…That is to say, people who have high self-rumination levels put the blame on self for negative circumstances, and then they feel as abject, wicked, hopelessness and etc. Previous studies indicated relationships between self-rumination and maladaptive constructions such as major depression (Mori & Tanno, 2015;Takano & Tanno, 2009), anxiety (Vassilopoulos, 2008, unhappiness (Elliott & Coker, 2008), low self-esteem (Joireman, Parrot, & Hammersla, 2002), and dysfunctional interpersonal relations (Lyubomirsky & Nolen-Hoeksema, 1995).…”
Section: Ruminationmentioning
confidence: 99%
“…Self-focused attention has been defined as "an awareness of self-referent, internally generated information that stands in contrast to an awareness of externally generated information derived through sensory receptors" (Ingram, 1990, p. 156). In this context, self-rumination is asserted as a threat for stability of self (Mori & Tanno, 2015). Self-rumination, in addition to rumination, includes negative beliefs of self, such as guiltiness, inferiority, indecency (Sarıçam, 2014).…”
Section: Ruminationmentioning
confidence: 99%